AN ALL HUMAN 3D IN VITRO MODEL OF THE BLOOD BRAIN BARRIER IN NANOPARTICLE DELIVERY AND CANCER METASTASIS STUDIES - Pilkington, Geoffrey John (Oxford University Press, 2014)
BACKGROUND: The blood-brain barrier (B-BB) is a dynamic functional unit consisting of endothelial cells, astrocytic endfeet and pericytes embedded in a specialized basement membrane. Most in vitro studies examine the ability of therapeutics to cross the B-BB using monolayer cultures or mixed species co-cultures and rely on Trans-Endothelial Electrical Resistance (TEER) measurements without verification of tight-junction (TJ) formation. More reliable high throughput in vitro models are therefore essential in brain tumour drug delivery and metastatic tumour behavioural studies. We are developing and testing a 3-dimensional in vitro model incorporating aspects of known B-BB in vivo characteristics. METHODS: A 3D model of the B-BB was constructed using human brain endothelial cells (hCMEC/D3), human astrocytes (SC-1800/UP010) and human brain vascular pericytes (HBVP) in mono-, co-, tri- cultures. TEER values were measured using a cell monitoring system- cellZscope(®). TJ proteins (ZO-1 and occludin) were examined by Western blotting and immunocytochemistry. Effects of extracellular matrix (ECM) molecules (laminin, fibronectin, collagen type IV, agrin, perlecan) were assessed on endothelial cell proliferation, adhesion and TEER changes using an Electric Cell-Substrate Impedance Sensing (ECIS) system. Modified chitosyme nanoparticles and metastatic lung cancer cells were tested for effects on B-BB integrity. RESULTS: Co-cultures and tri-cultures resulted in significantly higher TEER values compared to endothelial cells alone (p < 0.05). TEER values for co-culture of ECs and astrocytes were 4620 Ω/cm2, and for tri-cultivation including pericytes, 4141.50 Ω/cm2 compared to single EC cultures (2244 Ω/cm2). Western blot revealed higher expression of ZO-1 and occludin in co- and tri-cultures. The individual optimal ECM concentrations for highest and longest TEER values differed depending on ECM molecule and concentration. Cell adhesion (%) correlated with TEER values. Recovery time of B-BB integrity following chitosyme nanoparticle/metastatic cell treatment, differed in mono-, co-, tri-cultures. CONCLUSIONS: Astrocytes contribute to B-BB formation in this in vitro model. Motile pericytes may positively or negatively influence barrier formation or TJ tightness. ECM has varied and profound effects on TEER values. Multiple measures are needed to confirm TJ formation in addition to TEER values as these may not reflect ‘true’ B-BB integrity. Using compounds with known low B-BB penetration and analysing TJ protein expression in combination with novel therapeutics will aid in providing meaningful data to bridge the gap between drug discovery and pre-clinical studies. In addition, our brain metastatic research group utilizes this model to test effect of CD15 knockdown in lung metastatic cells on endothelial cell adhesion and B-BB passage. SECONDARY CATEGORY: Tumor Biology.